2000
DOI: 10.1007/s002440010139
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Use the Red Fox as a Bioindicator of Organochlorines?

Abstract: The exposure of red foxes to hexachlorobenzene (HCB), dichlorodiphenyltrichloroethan (DDT), DDT derivatives, and polychlorinated biphenyls (PCBs) in central Italy was determined by analyzing muscle and adipose tissue samples from 57 red foxes collected in 1992-1993 in three areas of Tuscany, each characterized by different levels of anthropization. Chemical analysis showed that HCB occurred in low concentrations, ranging from an average of 0.08 microg/g lipid basis in fat of foxes from Pisa, the least agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…For several years, remobilization of existing pollutants and their constant circulation in the environment and food web has been considered to represent the major source of PCB contamination in Switzerland (Müller 1994). In agreement with the general reduction of PCB exposure, we found a considerably lower PCB content in our study, conducted with samples obtained in 1999-2000, than in similar reports from neighboring countries (Germany and Italy) based on foxes collected during 1983(Brunn et al 1991Corsolini et al 1999Corsolini et al , 2000Georgii et al 1994). No adverse health or reproductive responses are expected to occur from this low burden of organochlorine contamination, and in fact, the local fox population in Zürich has been growing steadily during the last years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For several years, remobilization of existing pollutants and their constant circulation in the environment and food web has been considered to represent the major source of PCB contamination in Switzerland (Müller 1994). In agreement with the general reduction of PCB exposure, we found a considerably lower PCB content in our study, conducted with samples obtained in 1999-2000, than in similar reports from neighboring countries (Germany and Italy) based on foxes collected during 1983(Brunn et al 1991Corsolini et al 1999Corsolini et al , 2000Georgii et al 1994). No adverse health or reproductive responses are expected to occur from this low burden of organochlorine contamination, and in fact, the local fox population in Zürich has been growing steadily during the last years.…”
Section: Discussionsupporting
confidence: 92%
“…Organochlorine concentrations were assessed in samples of homogenized kidney using a validated procedure that follows the method by Corsolini et al (2000) with several modifications. Samples were extracted in the presence of a mixture of n-hexane and dichloromethane at a ratio of 4:1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to estimate the level of pollutants in an area, Corsolini et al, 2000). If so, the overall similarity between the spectrum of food habits in Leinati et al (I960) and our study could suggest that modest changes have occurred in the habitats within this large protected area.…”
Section: Discussionsupporting
confidence: 51%
“…Several animal species have been suggested to be suitable for the monitoring of environmental pollution. Mussels (Dreissena polymorpha) (Binelli et al, 2001;Szefe et al, 2002); herrings (Clupea harengus), and partridges (Alectoris rufa) (Herrera et al, 2000) or even mammals such as cattle (López-Alonso et al, 2002) and fox (Corsolini et al, 2000) have been suggested for the monitoring of environmental pollution. Since 1970, honeybees (Apis mellifera) have increasingly been used to monitor heavy metal environmental pollutants as reported in some studies (Porrini et al, 2002;Bromenshenk et al, 1985).…”
Section: Introductionmentioning
confidence: 99%